High-Strength Epoxy Nanocomposites Reinforced with Photochemically Treated CNTs - Lee, Jae Won; Kim, Sung-Soo; Lee, Min Wook; Hwang, Jun Yeon; Moon, Sook Young (ACS Publications, 2023)
A carbon nanotube (CNT)/epoxy nanocomposite was preparedusinga photochemical surface modification process of CNTs. The vacuum ultraviolet(VUV)-excimer lamp treatment created reactive sites on the CNT surface.Increasing the irradiation time increased the oxygen functional groupsand changed the oxygen bonding state such as C O, C-O,and -COOH. By the VUV-excimer irradiation on CNTs, the epoxyinfiltrated well between the CNT bundles and formed a strong chemicalbond between CNT and epoxy. The tensile strength and elastic modulusof the nanocomposites with VUV-excimer irradiated sample during 30min (R30) were found to increase by 30 and 68% compared to using pristineCNT, respectively. R30 was not pulled out and remained embedded inthe matrix until the fracture occurred. The VUV-excimer irradiationis an effective surface modification and functionalization methodfor improving the mechanical properties of CNT nanocomposite materials.